The evolution of deserts with climatic changes in China since 150 ka B.P - 董光荣 陈惠忠 王贵勇 李孝泽 邵亚军 金炯 (Science China. Earth sciences, 1997)
According to the bioclimatic zones, dune mobility and the fabric characteristics of stratigraphic sedimentary facies, the deserts in China are divided into Eastern, Western, Central and Northwestern deserts. Based on the records of stratigraphical facies, climatic proxies, historical data, etc. in each desert region, the evolution of deserts with climatic changes in time and space since 150 ka B. P. in China are dealt with; then the evolution of deserts in relation to the glacial climatic fluctuations caused by solar radiation changes, underlying surface variation and their feedback mechanism is discussed through comparison with global records; finally, in consideration of global wanning due to increasing of greenhouse gases such as CO2, the possible tendency of the evolution of deserts and the climatic changes is discussed.